Serum sortilin as a predictor of stroke in patients with intermediate carotid artery stenosis. (April 2023) - Şimsek, Zeki; Alizade, Elnur; Abdurahmanova, İlahe; Güner, Ahmet; Zehir, Regayip; Pala, Selçuk
Background: Sortilin was an important molecular protein involved in the pathogenesis of atherosclerosis. Besides, serum sortilin was associated with adverse cerebrovascular events. Atherosclerotic stenosis in the carotid artery is a major etiology for ischemic stroke. The risk of stroke in patients with intermediate carotid artery stenosis (CAS) was unknown. Hence, the aim of the present study was to evaluate the relationship between serum sortilin levels and stroke in patients with intermediate CAS. Methods: A total of 195 intermediate CAS patients were included in this cross-sectional study. The patients were divided into two groups as symptomatic ( N = 95) and asymptomatic ( N = 100) patients. Patients with a transient ischemic attack (TIA), retinal ischemic event, or ischemic stroke resulting from the narrowed carotid artery were considered to be symptomatic. Serum sortilin concentrations were measured using the enzyme-linked immunosorbent assay. Results: Serum sortilin level was significantly higher in the symptomatic group than in the severe asymptomatic group (1.53 ± 0.25 ng/mL vs 1.34 ± 0.19 ng/mL, p < 0.001). Besides, high serum sortilin levels (odds ratio = 4.91, 95% confidence intervals 1.24–19.51, p = 0.023) were identified as independent predictors of symptomatic carotid plaque. In the receiver operating characteristic curve analysis, serum sortilin levels higher than 1.34 ng/mL predicted stroke/TIA with a sensitivity of 66.3% and a specificity of 67% (AUC = 0.725, p < 0.001). Conclusions: Serum sortilin level is increased in the presence of symptomatic intermediate CAS and may have clinical value in the management of patients with carotid artery disease.